Synthesis of Al/Fe Pillared Bentonite: Characterisation and Analysis of Thermodynamic Parameter. Issue 1 (June 2021) - Said, M; Saputri, L I; Purwaningrum, W; Riyanti, F; Hariani, P L
Abstract: The modification of bentonite by pillarization process of Al/Fe metal oxide has been carried with metal oxide with ratios 1:2 and 2:1. The product was characterized by FT-IR, XRD and pHpzc analysis. Thus, this optimal pillarization product was used as an adsorbent of Congo red and Direct green dyestuffs. The FTIR characterization does not show optimum pillarization processes for any metal oxide ratios, while the XRD analysis shows the optimum pillarization processes at ratio 2:1 i.e. 17.1 Å. In addition, the optimum pH for absorption of Congo red took place at 2 while for Direct green at 3. At 70oC, the highest adsorption capacity (Qe) reached 57.34 and 72.06 mol/g; and the highest adsorption energy (E) was found 3.23 kJ/mol and 4.14 kJ/mol for Direct green for Congo red and Direct green, respectively. Vice versa, the enthalpy (ΔH) and entropy (ΔS) values decreased as the increase of both Congo red and Direct green concentration.